2021
DOI: 10.1097/gme.0000000000001790
|View full text |Cite
|
Sign up to set email alerts
|

Predictive and criterion validity of the Cervantes-SF menopause quality of life questionnaire

Abstract: The AEEM group responsible for the development of the Cervantes-SF scale is composed of: Pluvio J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In particular, the FLAVIE study revealed a significant reduction in the vasomotor, psychosocial and physical domains of the MENQoL scale, both at 4 weeks and 12 weeks since treatment was initiated. Likewise, the Cervantes Scale is the most frequently used validated menopause-QoL scale in the Spanish population and in Spanish-speaking countries [ 26 30 ]. Strikingly, an overall significant decrease in the global score of this scale, exceeding 25 points, was found at 12 weeks (35.4% improvement); it was noteworthy in the M&H domain (mean 17.4 points), and specifically in the reduction of VMS subdomain (–47.3%, mean 6.8 points).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the FLAVIE study revealed a significant reduction in the vasomotor, psychosocial and physical domains of the MENQoL scale, both at 4 weeks and 12 weeks since treatment was initiated. Likewise, the Cervantes Scale is the most frequently used validated menopause-QoL scale in the Spanish population and in Spanish-speaking countries [ 26 30 ]. Strikingly, an overall significant decrease in the global score of this scale, exceeding 25 points, was found at 12 weeks (35.4% improvement); it was noteworthy in the M&H domain (mean 17.4 points), and specifically in the reduction of VMS subdomain (–47.3%, mean 6.8 points).…”
Section: Discussionmentioning
confidence: 99%
“…All this fulfils the study objectives. In the analysis by the AEEM [ 26 ], a change of 6.7 points in the global Cervantes Scale score involved a significant improvement in accomplishing working/daily activities, a reduction in healthcare needs and alleviation of the economic burden resulting from menopausal symptoms and lost productivity. According to this analysis, the effectiveness of this food supplement containing soy isoflavones, 8-PN and melatonin would appear to be of notable clinical relevance, as the benefits in the vasomotor subdomain alone reached that score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is scored on a Likert scale from 0 to 5. 38 For negative questions, 0 indicates the best situation and 5 indicates the worst one. For positive questions, 0 is the worst possible situation and 5 is the best one.…”
Section: Cervantes Short Formmentioning
confidence: 99%
“…Menopausal hormone therapy (HT) could be used to improve health-related quality of life in perimenopausal and postmenopausal women 1-3 according to the statements of international scientific societies 4-6 . Many midlife women are taking or will take medications for other conditions when HT is recommended; however, data about possible interactions are scarce.…”
mentioning
confidence: 99%